EFFECTS OF INNOVATIVE APPROACHES IN CLASSES ON STUDENTS' SUCCESS: Examples of Sculpture Drawing Classes - UZ, Nurbiye; CIMENCI, Hasan (Journal of Education Culture and Society, 2018)
ABSTRACTConcept: Drawing is the foundation of plastic arts. The drawing class is one of the art education fields where students focus on observation, questioning, research and developing imagination. It can be seen that artists too are presenting different premises after drawing, which is generally considered as a preliminary to a work of art, being acknowledged as art by itself.Aim: The point of origin of this research is the inability of the students of sculpture departments to fully comprehend the importance of drawing with regard to the creating of a sculpture. The principal purpose is the explaining of the applied studies that are specifically designed to develop individual perspectives, drawing skills, personal lines and creativity of the students and the alternative methods of drawing which yield positive result.Methods: Instead of repeating the knowledge that students obtained via traditional methods, studies are approached where they can reinterpret and develop their knowledge in respect of the time, technique, perception etc. Drawings that are presented in line with the main purpose via innovative approaches are evaluated with a qualitative research.Conclusions: After briefly mentioning education and art education in this study, methods applied with an innovative approach in sculpture design courses are explained through selected examples. At the end of the studies, it was seen that the students were more active, eager to learn, courageous, questioning and every time they are applied, methods are resulted positively.